CONTENT ANALYSIS ON ENGLISH SKILLS FOR THE FUTURE FOR SENIOR HIGH SCHOOL/ ALIYAH GRADE XI LANGUAGE AND CULTURE PROGRAM - Anita Anita; Rina Fitriana (Sean Institute, 2023)
The aim of the research was to find out that “English Skills for the Future” met the evaluation criteria according to experts. Data collected by designing evaluation criteria that contained standard criteria for evaluating English textbooks and explaining its relevance to the 2013 English curriculum material. The researcher found that it met 66.7% of the criteria for English as a Foreign Language (EFL). ). There are eight criteria, namely (1) goals and approaches, (2) design and organization, (3) language content, (4) skills, (5) topics, (6) methodology, (7) practical considerations, and (8) instructions. Then, 33.3% of these textbooks do not meet the criteria of a good EFL textbook. It is categorized as